Analyzing Inventory Material Management Control Techniques on Residential Construction Project Using SPSS - Subramani, T; Suresh Kumar, T (International Journal of Engineering and Technology, 2018)
Building Construction materials adopted 50% of cost from the total estimation of the project. Estimated Cost and planned schedule can be achieved by effective material management. The project team must be understood the goals and efficient material management techniques for successful project execution. A well planned material management possible by on time delivery and equipment to the job site and improved workforce planning increased labor productivity, planned schedules and minimum cost. Questionnaire were prepared for data analysis based on Likert’s scale 25 respondents were answered the questionnaire. Collected data analyzed using SPSS.To reveal the respondents responses for enhance the analysis results used there are Frequency analysis, Factor analysis, and reliability analysis. Results will be obtained and also recommendations will be suggested.
Keywords: Analyzing; Inventory; Control Techniques; Project and SPSS.